Achieving Self-Sufficiency in Energy Production: Adapting to the Technology of Hydraulic Fracturing - Arora, Kanika (Digital Repository of Theses, 2024)
The present study has illustrated that self-sufficiency has played a significant role in human society. It highlights the aim and purpose of this thesis. Arab Oil Embargo and Russian Supply Cuts have resulted in creating self-sufficiency in the energy sector as early as 1970. The dependency on the supply of energy can be reduced with strategies of mergers and acquisitions. The current research has defined that hydrocarbons could be a potential source that can drive the conveyance and generate electricity. Global energy players and governmental institutions have identified alternate sources of energy such as wind energy and solar energy. To provide more solutions to the problem of relying on crude oil and other renewable resources for energy production is the purpose of this thesis. Some of the research questions that have been answered through this research are; What strategies are you using to extract a high quantity of shale gas? What is the true meaning of being energy self-sufficient for a nation?, and What competitive strategies to increase profit margins and achieve high efficiencies? It can be determined that the application of these useful energy sources assists in decreasing a high level of pollution. Those engaged in such research have examined the viability of wind energy in the North Sea in the UK. The sector of global energy typically suggests both essential scopes and severe challenges. The shale revolutions define the “hydraulic fracturing” and horizontal drilling” that assist the USA in enhancing their production of “oil” and “natural gas”. It has been estimated that the application of “Cradrilla Energy” is mainly utilized for hydraulic fracturing to facilitate the potential production of shale gas in the UK. This research aims to explore the impact of using hydraulic fracturing as an alternate source of energy and enlist the challenges that such an effort would entail. Based on the research, the outcomes have been mixed where the UK can produce shale gas through hydraulic fracturing if they take help from other nations as well as keeping their research active in this field. Keywords: Energy, wind energy, solar energy, hydraulic fracturing, oil and gas